# RL High-pass Filter

$$u(t)$$Instead of $$\Delta v(t)$$, we use the European symbol for voltage difference: $$u$$. The letter ‘u’ stands for “Potentialunterschied”.

### Trigonometry method, example 2

$$\require{AMSsymbols} \def\lfz#1{\overset{\Large#1}{\,\circ\kern-6mu-\kern-7mu-\kern-7mu-\kern-6mu\bullet\,}} \def\lfzraised#1{\raise{10mu}{#1}} \def\laplace{\lfz{\mathscr{L}}} \def\fourier{\lfz{\mathcal{F}}} \def\ztransform{\lfz{\mathcal{Z}}} \def\crw{\lfz{}} \require{cancel} \newcommand\ccancel[2][black] {\color{#1}{\cancel{\color{black}{#2}}}} \newcommand\ccancelto[3][black] {\color{#1}{\cancelto{#2}{\color{black}{#3}}}}$$Assume the non-homogeneous linear differential equation of a first order High-pass LC-filter, where $$u(t)=\hat{u}\cos(\omega t)$$ is the forcing function and the current $$i(t)$$ through the inductor is the response. The differential equation for this system is $$L\,{i_p}^\prime(t)+R\,i_p(t)=\hat{u}\cos(\omega t)\label{eq:bTrigRL_DV}$$ The solution is a superposition of the natural response and a forced response. The so called, homogeneous solution $$y_h(t)$$ and the particular solution $$i_p(t)$$ $$i(t)=i_h(t)+i_p(t)\label{eq:bTrigRL_hp}$$

#### Homogeneous solutions

The homogeneous solutions follows from the reduced (=homogeneous) linear differential equation where the forcing function is zero. $$L\,{i_p}^\prime(t)+R\,i_p(t)=0\label{eq:bTrigRL_homDV}$$ According the Euler, the homogeneous solutions are in the form $$i_h(t)=\mathrm{e}^{pt}\label{eq:bTrigRL_gen}$$ substituting this $$i_h(t)$$ in $$\eqref{eq:bTrigRL_homDV}$$ gives the characteristic equation with root $$p$$ \begin{align} L\,(\mathrm{e}^{pt})^\prime+R\,\mathrm{e}^{pt}&=0\nonumber\\ \Rightarrow\quad L\,p\mathrm{e}^{pt}+R\,\mathrm{e}^{pt}&=0&\div{\mathrm{e}^{pt}}\nonumber\\ \Rightarrow\quad L\,p+R&=0\nonumber\\ p&=-\frac{R}{L}\label{eq:bTrigRL_p} \end{align} The solution base $$i_{h,1}(t)$$ follows from substituting the root $$p$$ from equation $$\eqref{eq:bTrigRL_p}$$ in back in the homogeneous differential equation $$\eqref{eq:bTrigRL_gen}$$ $$i_{h1}(t)=\mathrm{e}^{pt}=\mathrm{e}^{-\frac{R}{L}t}$$ The homogeneous solution follows as a linear combination of the solution bases (only one in this case) as $$i_h(t)=c\,i_{h1}(t)=c\,\mathrm{e}^{-\frac{R}{L}t}\label{eq:bTrigRL_hSolution}$$ where the constant $$c$$ follows from the initial conditions.

#### Particular solutions

If we force a signal $$\hat{u}\cos(\omega t)$$ on a linear system, the output will have the same frequency but with a different phase $$\phi$$ and amplitude $$A$$. \begin{align} i_p(t)&=A\cos(\omega t+\phi)\label{eq:bTrigRL_form}\\ \Rightarrow\quad i^\prime_p(t)&=-A\,\omega\sin(\omega t+\phi)\label{eq:bTrigRL_formDer} \end{align} Substituting $$(\ref{eq:bTrigRL_form},\ref{eq:bTrigRL_formDer})$$ in the differential equation $$\eqref{eq:bTrigRL_DV}$$ \begin{align} -AL\,\omega\sin(\omega t+\phi)+AR\cos(\omega t+\phi)&=\hat{u}\cos(\omega t)\nonumber\\ \Rightarrow\quad \color{green}{R}\cos(\omega t+\phi)-\color{green}{\omega L}\,\sin(\omega t+\phi)&=\frac{\hat{u}\cos(\omega t)}{A}\label{eq:bTrigRL_part}\\ \end{align} Work towards the trigonometric identity
\begin{align} C\cos(\alpha+\beta)=C\cos\alpha\cos\beta-C\sin\alpha\sin\beta\nonumber \end{align}\nonumber
by assigning the two independent variables $$R$$ and $$\omega L$$ to two more convenient independent variables $$C\cos\alpha$$ and $$C\sin\alpha$$ \begin{align} C\cos\alpha&\triangleq R\label{eq:bTrigRL_CcosAlpha}\\ C\sin\alpha&\triangleq\omega L\label{eq:bTrigRL_CsinAlpha}\\ \end{align} to dot the ‘i’, introduce $$\beta$$ $$\beta\triangleq\omega t+\phi\label{eq:bTrigRL_beta}$$ we can rewrite $$\eqref{eq:bTrigRL_part}$$ and use the aforementioned trigonometric identity \begin{align} C\cos\alpha\cos\beta- C\sin\alpha\sin\beta&=\frac{\hat{u}\cos(\omega t)}{A}\nonumber\\ C\cos(\alpha+\beta)&=\frac{\hat{u}\cos(\omega t)}{A}\label{eq:bTrigRL_alpabetaC}\\ \end{align} Divide $$\eqref{eq:bTrigRL_CsinAlpha}$$ by $$\eqref{eq:bTrigRL_CcosAlpha}$$ to solve for $$\alpha$$, and apply the geometric identity $$\sin^2\alpha+\cos^2\alpha=1$$ to $$\eqref{eq:bTrigRL_CsinAlpha}$$ by $$\eqref{eq:bTrigRL_CcosAlpha}$$ to solve for $$C$$ \begin{align} \frac{\cancel{C}\sin\alpha}{\cancel{C}\cos\alpha}=\frac{\omega L}{R} \quad\Rightarrow\quad \alpha&=\arctan\left(\frac{\omega L}{R}\right)\label{eq:bTrigRL_alpha} \\ \left(\frac{R}{C}\right)^2+\left(\frac{\omega L}{C}\right)^2=1 \quad\Rightarrow\quad C&=\sqrt{R^2+(\omega L)^2}\label{eq:bTrigRL_C} \end{align} Substituting $$(\ref{eq:bTrigRL_beta}, \ref{eq:bTrigRL_alpha},\ref{eq:bTrigRL_C})$$ in equation $$\eqref{eq:bTrigRL_alpabetaC}$$ \begin{align} \sqrt{R^2+(\omega L)^2}\,\cos\left(\arctan\frac{\omega L}{R}+\omega t+\phi\right)&=\frac{\hat{u}\cos(\omega t)}{A}\nonumber\\ \color{brown}{A}\,\cos\left(\color{teal}{\arctan\frac{\omega L}{R}+\omega t+\phi}\right) &=\color{brown}{\frac{\hat{u}}{\sqrt{R^2+(\omega L)^2}}}\,\cos(\color{teal}{\omega t})\nonumber\\ \end{align} and combine like terms \begin{align} A&=\frac{\hat{u}}{\sqrt{R^2+(\omega L)^2}}\label{eq:bTrigRL_A}\\ \arctan\frac{\omega L}{R}+\cancel{\omega t}+\phi=\cancel{\omega t} \quad\Rightarrow\quad \phi&=-\arctan\left(\frac{\omega L}{R}\right)\label{eq:bTrigRL_Phi}\\ \end{align} The particular solution follows from substituting $$(\ref{eq:bTrigRL_A},\ref{eq:bTrigRL_Phi})$$ in $$\eqref{eq:bTrigRL_form}$$ \begin{align} i_p(t)&=A\cos(\omega t+\phi)\nonumber\\ \text{where}\quad A&=\frac{\hat{u}}{\sqrt{R^2+(\omega L)^2}}\nonumber\\ \text{and}\quad&\phi=-\arctan\left(\frac{\omega L}{R}\right)\nonumber \end{align}\label{eq:bTrigRL_pSolution}

#### General solution

Substituting equation $$(\ref{eq:bTrigRL_hSolution},\ref{eq:bTrigRL_pSolution})$$ in equation $$\eqref{eq:bTrigRL_hp}$$ gives the general solution for $$i(t)$$ \begin{align} i(t)&=c\,\mathrm{e}^{-\frac{R}{L}t}+A\cos(\omega t+\phi)\nonumber\\ \text{where}\quad A&=\frac{\hat{u}}{\sqrt{R^2+(\omega L)^2}}\nonumber\\ \text{and}\quad&\phi=-\arctan\left(\frac{\omega L}{R}\right)\nonumber \end{align} This seems like a good moment in time to start looking for a less involved method of solving these non-homogeneous differential equations. In the next section we will find such a method by using a complex forcing function.

### Complex arithmetic method

We will demonstrate this method using a RL high-pass filter, with input $$u(t)=\hat{u}\cos(\omega t)$$ and output current $$i(t)$$ through the inductor. The differential equation for this system is $$L\,{i_p}^\prime(t)+R\,i_p(t)=\hat{u}\cos(\omega t)\label{eq:bRLDV}$$ Using the complex source $$\hat{u}\,\mathrm{e}^{j\omega t}$$, the corresponding complex response is of the form \begin{align} i_p(t)&=A\,\mathrm{e}^{j(\omega t+\phi)}\\ \Rightarrow\quad {i_p}^\prime(t)&=j\omega\,A\,\mathrm{e}^{j(\omega t+\phi)}\\ \end{align} Substituting these in $$\eqref{eq:bRLDV}$$ \begin{align} L\,j\omega\,A\,\mathrm{e}^{j(\omega t+\phi)}+R\,A\,\mathrm{e}^{j(\omega t+\phi)}&=\hat{u}\mathrm{e}^{j\omega t},&\div\mathrm{e}^{j\omega t}\nonumber\\ \Rightarrow\quad j\omega L\,A\,\mathrm{e}^{j\phi} +R\,A\,\mathrm{e}^{j\phi}&=\hat{u}\nonumber\\ \Rightarrow\quad A\,\mathrm{e}^{j\phi}(j\omega L+R)&=\hat{u}\nonumber\\ \Rightarrow\quad A\,\mathrm{e}^{j\phi}&=\frac{\hat{u}}{j\omega L+R} \end{align} The amplitude $$A$$ and phase $$\phi$$ of the response are found as \begin{align} A&=\left|\frac{\hat{u}}{j\omega L+R}\right|\\ \phi&=\angle\hat{u}-\angle(j\omega L+R) =0-\mathrm{atan2}\left(\omega L,R \right) =\arctan\left(\frac{\omega L}{R}\right) \end{align} So that the complete response of the system is \begin{align} i_{ss}(t)&=A\,\mathrm{e}^{j(\omega t+\phi)},\nonumber\\[6mu] \text{where}\quad A&=\left|\frac{\hat{u}}{j\omega L+R}\right|=\hat{u}\frac{1}{\sqrt{(\omega L)^2+R^2}},\nonumber\\ \text{and}\quad\phi&=\angle\hat{u}-\angle(j\omega L+R) =0-\mathrm{atan2}\left(\omega L,R \right) =-\arctan\left(\frac{\omega L}{R}\right)\nonumber \end{align}\label{eq:bRLSol} Since the real forcing function was $$\cos$$, the real part of $$\hat{u}\cos(\omega t)+j\,\hat{u}\sin(\omega t)$$ we need to extract the real part of the solution equation $$\eqref{eq:bRLSol}$$ \begin{align} i_{ss}(t)&=A\,\cos(\omega t+\phi),\nonumber\\[6mu] \text{where}\quad A&=\frac{\hat{u}}{\sqrt{(\omega L)^2+R^2}},\nonumber\\ \text{and}\quad\phi&=-\arctan\left(\frac{\omega L}{R}\right)\nonumber \end{align} [link]
Embedded software developer
Passionately curious and stubbornly persistent. Enjoys to inspire and consult with others to exchange the poetry of logical ideas.

This site uses Akismet to reduce spam. Learn how your comment data is processed.